2018
DOI: 10.1093/nar/gky1258
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneity ofattCintegron recombination sites revealed by optical tweezers

Abstract: A predominant tool for adaptation in Gram-negative bacteria is the functional genetic platform called integron. Integrons capture and rearrange promoterless gene cassettes in a unique recombination process involving the recognition of folded single-stranded DNA hairpins—so-called attC sites—with a strong preference for the attC bottom strand. While structural elements have been identified to promote this preference, their mechanistic action remains incomplete. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…These endonucleases have previously been used to introduce a modification in a DNA construct (23), e.g. a quantum dot, or to insert a small hairpin (36), but not to generate long ssDNA’s to synthesize either a full length coilable dsDNA or a long DNA hairpin based on annealing. To this end, we have designed a DNA plasmid with regularly interspaced insertions of BbvCI nicking sites (5′-CCTCAGC-3′).…”
Section: Resultsmentioning
confidence: 99%
“…These endonucleases have previously been used to introduce a modification in a DNA construct (23), e.g. a quantum dot, or to insert a small hairpin (36), but not to generate long ssDNA’s to synthesize either a full length coilable dsDNA or a long DNA hairpin based on annealing. To this end, we have designed a DNA plasmid with regularly interspaced insertions of BbvCI nicking sites (5′-CCTCAGC-3′).…”
Section: Resultsmentioning
confidence: 99%
“…FD curves were fitted using a custom written Python script, which is based on Pylake package provided by Lumicks (https://lumicks-pylake.readthedocs.io/). The fitting procedure was done as described in (Mukhortava et al, 2019). In brief, first, a fully folded part (until the first detectable unfolding step) was fitted with a worm-like chain model (WLC) (Odijk, 1995; Wang et al, 1997) to determine the persistence length (dsL P ) of the tether while the contour length (dsL C ) parameter was held fixed at 1256 nm (± 1%; 4110 bp*0.305 nm/bp and 4 ss*0.59 nm/ss) (Zhang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have already suggested that attC site recombination frequency depends on numerous properties related to their sequence, structure, and stability ( 6 , 8 , 9 , 11 , 12 , 25 , 26 , 40 , 41 ). Most of these factors apply to both attI × attC and attC × attC recombination reactions.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, we have observed large changes in recombination frequency (one to three orders of magnitude) upon modification of essential attC site elements: the 5′-AAC-3′ triplet of the R box ( 12 ), the stem ( 6 , 42 ), the EHBs ( 8 , 9 ), and the overall recombinogenic folding ( 25 ). On the other hand, we have identified features of attC sites that are highly conserved and play an important role in recombination, and yet, their disruption does not produce more than twofold differences in recombination: the high GC content in the apical part of the stem ( 40 ), the nucleotide skew within the unpaired regions ( 8 ), and the overall propensity to form a straight hairpin ( 41 ). The present study identified attC site mutations that are responsible for substantial (up to 12-fold) changes in recombination frequency, which places the uncovered properties among the most important ones.…”
Section: Discussionmentioning
confidence: 99%